(untitled) (American Journal of Arts and Human Science, 2022)
This study aims to determine the relationship between gender and dance motivation to dance style choices of 85 students taking Bachelor of Performing Arts at City College of Angeles. The study was conducted through an online survey using Dance Motivation Questionnaire (DMQ). Frequency and percentage were used to describe the gender of the respondents, while Mean and Standard Deviation were used to describe the level of dance motivation, and ANOVA and Pearson’s Chi-Square was used to determine the relationship between Dance Motivation and Gender to Dance Style Choices respectively. From the data obtained from the online survey questionnaire, it was found out there are 38 (n=44.71%) male and 47 (n=55.29%) female who answered the online survey. It was also found out that most of the respondents chose Hip-hop as their preferred dance style. The level of dance motivation of the respondents was found out to be moderately high. It was also found out that age and dance motivation have a significant relationship to students’ dance style choice. Also, it was found out that there is a difference in dance style choice of the respondents based on gender. Overall, It was concluded that the gender and dance motivation are considered determinants of the dance style choice of students. Results obtained from this study provide new information to students, teachers, dance enthusiasts and researchers who are interested in conducting studies pertaining to gender, dance motivation and dance style choice. Further investigation is highly recommended to support the findings of this study.